Reasons of Using IT Outsourcing (ITO) — Polish-Spanish Cross-Cultural Analysis - Słoniec Jolanta; González Rodriguez Reyes (Foundations of Management, 2018)
The article compares the reasons for using IT outsourcing (ITO) in Polish and Spanish enterprises, based on the authors’ own research. The reasons for the application of ITO have been classified into three groups: economic, technological, and organizational/strategic. On the basis of the classified reasons, a research hypothesis was formulated: Representatives of Polish enterprises assess other groups of reasons as the most important motivation for the use of ITO in their companies compared to Spanish enterprises. On the basis of the authors’ own research, the hypothesis has been confirmed. Polish enterprises assess technological reasons as the most important, whereas Spanish enterprises consider organizational/strategic reasons to be the most important, although the differences in the assessment are not large. The difference in the validity of the reasons for the use of ITO may arise from the maturity of the ITO market in both countries but may also result from the personal experience of the companies with ITO.